Implementation of Sticky Note Learning Media to Increase Reading Interest in 5th-Grade Students Towards Lesson Books in the Pandemic of Covid 19 - Aditia Ardiana; Asep Bayu Dani Nandiyanto; Tedi Kurniawan; Muhamad Roil Bilad (Universitas Pendidikan Indonesia (UPI), 2022)
Reading is fundamental for someone to get other abilities. However, there are still areas in Indonesia that are still lacking in reading. The purpose of the core research is to provide literacy learning innovations in 5th grade elementary school. carried out during the pandemic with an online learning system. Students are given learning with sticky notes, where sticky notes are used as the medium. Sticky notes contain questions that must be matched with other sticky notes based on the same color. From the description above, we use this approach to test the literature and theory to suit the circumstances of the location we are researching. This is why we use a quantitative approach. The quantitative approach in this study is to find out the extent to which the implementation of learning with Sticky Notes in increasing the reading interest of grade 5 students towards textbooks during the covid-19 pandemic. This approach emphasizes more on finding data to be processed systematically and using mathematical calculations. From the results of the study, students got an increase of 18% from the results of the pre-test. This is in line with the results of previous research and the method was successfully used for learning.